Fluktuasi Nilai Tukar Rupiah: Pengaruhnya Terhadap Keputusan Investasi Asing di Indonesia - Seri Ningsih (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2025)
This study aims to analyze the effect of Rupiah exchange rate fluctuations on foreign investment decisions in Indonesia during the 2015–2023 period. The research employed a quantitative approach using secondary time series data obtained from the Central Bureau of Statistics (BPS) and Bank Indonesia. The independent variable in this study is the Rupiah exchange rate against the United States Dollar, while the dependent variable is foreign direct investment (FDI). Data were analyzed using simple linear regression with the assistance of EViews 12 software, preceded by classical assumption tests, including normality, heteroscedasticity, and autocorrelation tests. The results indicate that the Rupiah exchange rate has a positive and statistically significant effect on foreign investment decisions in Indonesia, with a probability value of 0.0025 (<0.05) and a regression coefficient of 174.2583. The coefficient of determination (R²) of 0.7511 indicates that 75.11% of the variation in foreign investment decisions can be explained by fluctuations in the Rupiah exchange rate, while the remaining 24.89% is influenced by other factors outside the research model. These findings suggest that exchange rate stability is an important factor in enhancing foreign investor confidence and encouraging foreign investment inflows into Indonesia. Therefore, maintaining exchange rate stability should remain a key policy priority to support a favorable investment climate.